PERCANGANGAN PENJUALAN BARANG BANGUNAN BERBASIS WEB PADA TOKO BANGUNAN ENGGAL MAJU - Alvin Nicolaus; Hablan Maulana; Singgih Baskoro; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
This research is entitled, "Design of Web-Based Building Goods Sales at Enggal Maju Building Stores". The background of the problem at the Enggal Maju Building Store today is from the rapid development of technology that has an impact on all life, especially the provision of information for a company that requires a marketing and ordering system. To support effectiveness, productivity and efficiency in a company in solving ordering problems, especially providing services to the community, especially to the community to know more about the Enggal Maju Building Shop. This web-based Goods Ordering System aims to create an effective and efficient performance, because it is easier to get information and does not need to waste a lot of costs. Through this service, it is hoped that it will make it easier for the public to get complete and up-to-date, interactive, and dynamic information, it is hoped that the Enggal Maju Building Store can get more value from the satisfaction of the community to know more. This system can be more efficient in terms of cost, effort and time, so it is effective in achieving goals. In accessing the system so far, sometimes there are obstacles in implementing information.